Cash Transfer Programs and Household Labor Supply - Daniela Del Boca; Chiara Daniela Pronzato; Giuseppe Sorrenti (Center for Economic Studies and ifo Institute (CESifo), 2020)
Employment contributes to reduce the risk of poverty. Through a randomized controlled trial, we evaluate the impact of a conditional cash transfer program (CCT) to low-income families with dependent children on household members' labor supply. The attendance of labor-market-oriented mentoring courses constitutes the condition to obtain the transfer. One year after admission to the program, fathers assigned to the CCT program are more likely to work (+14 percent) than fathers assigned to an unconditional cash transfer program or to a pure control group. No effect arises for mothers. Increased paternal investments in activities enhancing labor market opportunities and improved family networks seem to explain the results.
Keywords: I10; I20; J24; I31; 330; conditional cash transfers; poverty; household labor supply; mentoring courses